RATIONAL EMOTIVE BEHAVIOR THERAPY DALAM MENANGGULANGI PERILAKU AGRESIF REMAJA - Intan Nur Aini; Samsul Arifin (Fakultas Dakwah Universitas Ibrahimy, 2023)
Adolescence is the peak of high emotional development, in early adolescence emotional development is very sensitive and reactive to events or social situations that are under pressure and new conditions. Their emotions tend to be negative and temperamental. This makes the teenager’s emotions often explode in the form of irritability and self-will that doesn’t want to be told. Every teenager is a person with individual growth patterns and timing, as well as personality, background and family experiences. Likewise in their behavior, the things that underlie or cause the emergence of a behavior in adolescents are of course also very diverse. Aggressive behavior for example. In general, aggressive behavior in adolescents tends to hurt other people, aggressive behavior can also deliberately vent one’s emotions. Aggressive behavior can be done by anyone, including teenagers. Factors that influence aggressive behavior are not only from within the individual but also from environmental influences. In our view, these problems can be overcome through the Rational Emotive Behavior Therapy (REBT) approach. Where in this approach focuses on the process of thinking and behavior. Irrational mindset will lead to a life that is not good. Conversely, a rational mindset will lead to a happy, comfortable and effective life. There are three techniques in this Rational Emotive Behavior Therapy (REBT) approach, cognitive techniques, emotive techniques and behavioral techniques. However, researchers only focus on one technique, namely cognitive techniques. The purpose of this research is that humans can live effectively and happily by having rational mindsets and behaviors about their lives. The results of this study are able to make clients reduce the habit of making counselees overcome aggressive behavior towards others, willing to listen if others tell them and also not saying harshly to other people.